House of the Surgeon, Pompeii : Excavations in the Casa Del Chirurgo (VI 1, 9-10. 23) - Anderson, Michael (Oxbow Books, Limited, 2017)
Intro -- Title -- Copyright -- CONTENTS -- Acknowledgements -- Preface -- Foreword: The Old Certainties are Crumbling: Rick Jones -- 1. Pompeii's Insula VI 1 and the Casa del Chirurgo: Michael A. Anderson and Damian Robinson -- 2. The Anglo-American Project in Pompeii: Damian Robinson, Michael A. Anderson, H.E.M. Cool, Robyn Veal, and Charlene Murphy -- 3. Digging the Casa del Chirurgo: Michael A. Anderson and Damian Robinson -- 4. The Stratigraphic and Structural Sequence of the Casa del Chirurgo: Michael A. Anderson and Damian Robinson -- 5. Room by Room Discussion of Stratigraphy and Architecture: Michael A. Anderson and Damian Robinson -- 6. Glass Vessels and Small Finds: H. E. M. Cool -- 7. Report on the Coinage Recovered from the AAPP Excavations in the Casa del Chirurgo: Richard Hobbs -- 8. Plaster Fragments from the Cisterns of the Casa del Chirurgo: a window onto the house's lost decoration: Helen White -- 9. Pavements of Mortar, Mosaic and Marble Inlay: Will Wootton -- 10. The Faunal Remains: Jane Richardson -- 11. Archaeobotanical Remains: Charlene Murphy -- 12. Fuel and Timber in the Casa del Chirurgo: Robyn Veal -- 13. The Ancient Campanian Environment and Results from the Casa del Chirurgo: Robyn Veal and Charlene Murphy -- 14 Conclusions: Michael A. Anderson -- Appendix I: Stratigraphic Unit Listing and Chapter 5 Concordance -- Appendix II: Harris Matrices for Areas Excavated -- Bibliography.